Strong-coupling study of the Gribov ambiguity in lattice Landau gauge - Maas, Axel Torsten; Pawlowski, Jan M.; Spielmann, Daniel (The European physical journal. C, Particles and fields, 2010)
We study the strong-coupling limit β=0 of lattice SU(2) Landau gauge Yang-Mills theory. In this limit the lattice spacing is infinite, and thus all momenta in physical units are infinitesimally small. Hence, the infrared behavior can be assessed at sufficiently large lattice momenta. Our results show that at the lattice volumes used here, the Gribov ambiguity has an enormous effect on the ghost propagator in all dimensions. This underlines the severity of the Gribov problem and calls for refined studies also at finite β. In turn, the gluon propagator only mildly depends on the Gribov ambiguity.
Gesehen am 05.12.2017